Merdeka for the mind essays on Malaysian struggles in the 21st century - Ooi, Kee Beng (Strategic Information and Research Development Centre, 2015)
This selection of articles written over the last three years by Ooi Kee Beng, and which were published in The Edge Malaysia, The Edge Review and in Penang Monthly, is a succinct expression, not only of trends that the region and the world are experiencing, but more specifically of stubborn issues immediately affecting Malaysia. In essence, Malaysia has reached a crossroads. The bankruptcy of racialist politics maintained for too long by race-based parties through racially-justified policies has become too obvious to deny. On the one hand, this has generated strong opposition from the depths of Malaysian society-from Malaysians who had customarily been evasive of conflicts, who now sense that serious political transformation can be postponed only at great peril to the country's inter-ethnic cohesion and to its economy. And on the other hand, as a direct response to this challenge to the old order, we witness a disheartening rise in incoherent racism and Islamist zealotry. But Malaysia's problems are not all that unique. What is needed is for Malaysia to discard its sense of exceptionalism and fatalism, if the country is to fulfil the promise that the attainment of Merdeka once held.